The Existence of Educational Financing Implementation in the Homeschooling System - H. Soro , Suharyanto; Dwi Utami, Puji Ratna; Maesaroh, Nimas (Civiliza Publishing, Indonesia., 2025)
In general, Homeschooling is a form of non-formal education that does not follow a structured financing system like formal education. After conducting an in-depth analysis of the implementation and sources of funding in the homeschooling system particularly in Homeschooling Focus, located in Arcamanik Subdistrict, Bandung City, this study uncovered compelling findings regarding the financial implementation of education. The purpose of this research is to identify how the financing system in Homeschooling Focus is carried out. This study employs a qualitative descriptive approach. The main findings reveal that the education financing system in Homeschooling Focus is implemented in a planned and organized manner, with execution that aligns with pre-established plans and includes evaluation stages, despite limited funding sources. Furthermore, the financing process is flexible while still upholding the principles of transparency, with all income and expenditure transactions properly recorded and supervised by the management team.